Nationalism and the Irish Party provincial Ireland, 1910-1916 - Wheatley, Michael (Oxford University Press, 2005)
Michael Wheatley examines Irish politics in the last years of the Union, before war and uprising transformed Irish and British politics. Focusing particularly on the Irish Party, he provides a detailed, scholarly analysis and challenges the view that the party was doomed and Home Rule was impossible to achieve.